Answers

2014-08-19T16:17:32+05:30
P(x) = x+3
p(-x) = -x+3
p(x)+p(-x) = (x+3)+(-x+3)
               = x+3-x+3
p(x)+p(-x) = 6
0
2014-08-19T16:18:39+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
P(X) =  X + 3 
This means that what ever is in the parenthesis on LHS is what X is on RHS.  Replace X on RHS with the expression within parenthesis on LHS.

P( 3 ab + 4 g - 8 k ) will be  =  (3 ab + 4 g - 8k)  + 3
============================================
P(X)  =  X  + 3
P(-X) =  (-X)  + 3    =  3 - X

P(X) + P(-X)     =  X + 3 + 3 - X = 6

1 5 1